New Stage Interpretation of a Classic Piece - Omonulla Rizaev (International Journal on Integrated Education, 2022)
The article discusses the interest in staging Shakespeare's works in Uzbek theaters, a new interpretation of his famous tragedy "King Lear", staged in the Uzbek Theater of the Samarkand region.